Penggambaran Masyarakat Kelas Atas di Korea Selatan pada Serial Class Of Lies - Syifa, Salsabila Ayu; Haloho, Heppy New Year (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2022)
Each country has a different measure to divide society based on its social class. Social class is divided into three parts, namely upper, middle, and lower social class. The purpose of this study is to describe the upper-class society in South Korea in the Class Of Lies series. This research approach uses descriptive qualitative with the semiotic method of Roland Barthes with the meaning of denotation, connotation, and myth. The results of this study indicate that the upper class is described as selfish, likes to abuse power, acts arbitrarily, abuse power, and does academic cheating. These characters are related to the realities that occur in South Korea, such as political scandals containing rulers, education as the standard of social class, and the spoon class theory which emphasizes the importance of parental background in determining children's social class position in social interactions system.